Multimodal Medical Imaging Security using Hybridization of Honey Encryption Algorithm with Binary Particle Swarm Optimization - et. al., Jayahari Prabhu G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transmitting and receiving information through any network requires some sort of security. One of the major application requires data security is Medical Imaging System. Especially, for owning any significant information about patient details. This Medical Imaging System does the operation of encryption and decryption, for which the security key has been built to protect information using numerous cryptographic algorithms. Choosing an algorithm for secured information correspondence, to attain quality parameters such as higher privacy, confidentiality, integrity and effectiveness. This work proposed by hybridization of Honey Encryption Algorithm with Binary Particle Swarm Optimization to scramble the restorative medical data. Comparatively, this proposed algorithm reduces the Mean Square Error (MSE) to 1% and increased the Peak Signal to Noise Ratio (PSNR) value to 98.7%. The subsequent operation is performed using Binary particle swarm optimization for overhauling the keys.